Efficacy and Safety of Bromocriptine-QR as an Adjunctive Therapy on Glycemic Control in Subjects with Uncontrolled Type 2 Diabetes Mellitus: A Systematic Review and Meta-analysis - Yanto, Theo Audi; Budiputri, Charista Lydia; Muljono, Michelle Patricia; Chandra, Shally (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Introduction. There has been an increasing awareness of the effects of combining bromocriptine-QR with other medications for diabetes mellitus type 2. This study aimed to assess the efficacy and safety of bromocriptine-QR as an adjunctive therapy for patients with uncontrolled type 2 diabetes mellitus. Methodology. This systematic review is registered at the International Prospective Register of Systematic Reviews (CRD42022360326). Literature search was done via MEDLINE, NCBI, Google Scholar, Science Direct, Europe PMC and Cochrane Library databases. We included randomized controlled trials with participants 18 years old and above with uncontrolled type 2 diabetes mellitus. The primary outcome of interest is the efficacy and safety of bromocriptine-QR as an adjunctive therapy for glycemic control. Case reports, case series, reviews and animal studies were excluded. The risk of bias was reviewed using the Cochrane Risk of Bias tool. Meta-analysis was performed using Review Manager 5.4 and presented as a weighted mean difference and 95% confidence interval for changes from the baseline level. Results. Nine studies were included in the systematic review with a total of 2709 participants. The baseline HbA1c in the bromocriptine-QR group was 7.42% and 7.51% in the control group. The bromocriptine-QR group was favoured, outperforming the control group in terms of reducing hemoglobin A1c(HbA1c), with a statistically significant difference (weighted mean difference -0.6%; 95% CI [-0.83,-0.36]; p<0.00001). The most common side effects were nausea (33.75% vs 6.92%), fatigue (13.11% vs 5.94%), and headache (11.17% vs 6.87%). Conclusion. Administration of bromocriptine-QR at a dose range of 1.6 to 4.8 mg/day as an adjunctive therapy reduced HbA1c and FBG in patients with uncontrolled type 2 diabetes mellitus (T2DM). However, there were also statistically greater odds of the occurrence of adverse events such as nausea, vomiting, and headache compared to controls.